Bond risk premia and restrictions on risk prices - Constantino Hevia; Martin Sola (Journal of Risk and Financial Management, 2018)
Researchers who estimate affine term structure models often impose overidentifying restrictions (restrictions on parameters beyond those necessary for identification) for a variety of reasons. While some of those restrictions seem to have minor effects on the extracted factors and some measures of risk premia, such as the forward risk premium, they may have a large impact on other measures of risk premia that is often ignored. In this paper, we analyze how apparently innocuous overidentifying restrictions imposed on affine term structure models can lead to large differences in several measures of risk premiums.
Keywords: E43; G12; 330; bond risk premia; affine term structure models; risk prices